MAPPING OF MOUTAIN AND FOOTHILL LANDSCAPES (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the theoretical and practical aspects of mapping mountain and foothill landscapes. It examines the structure of landscapes, the natural and anthropogenic factors affecting them, as well as the significance of modern cartographic technologies.